2023
DOI: 10.5751/es-13862-280130
|View full text |Cite
|
Sign up to set email alerts
|

Games for experiential learning: triggering collective changes in commons management

Abstract: As resource users interact and impose externalities onto each other, institutions are needed to coordinate resource use, create trust, and provide incentives for sustainable management. Coordinated collective action can play a key role in enabling communities to manage natural resource commons more sustainably. But when such collective action is not present, what can be done to foster it? We contribute to the understanding of how experiential learning through games can affect behavioral change, potentially lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Intensive pumping can draw down aquifer levels and follow pathways that are economically inefficient, socially inequitable, and environmentally unsustainable. (Van and Shah 2003); conventional regulation (Molle and Closas 2016); information-based (Andhra Pradesh Farmer Managed Groundwater Systems) (Venkata et al 2013;Verma et al 2012;Reddy, Pavelic, and Reddy 2021); Experiential learning (Ruth Meinzen-Dick et al 2018;FES 2022;Falk et al Forthcoming); Western India (Shah 2009;Shah et al 2018); North China Plain (Kinzelbach et al 2022).…”
Section: Tools and Toolkitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intensive pumping can draw down aquifer levels and follow pathways that are economically inefficient, socially inequitable, and environmentally unsustainable. (Van and Shah 2003); conventional regulation (Molle and Closas 2016); information-based (Andhra Pradesh Farmer Managed Groundwater Systems) (Venkata et al 2013;Verma et al 2012;Reddy, Pavelic, and Reddy 2021); Experiential learning (Ruth Meinzen-Dick et al 2018;FES 2022;Falk et al Forthcoming); Western India (Shah 2009;Shah et al 2018); North China Plain (Kinzelbach et al 2022).…”
Section: Tools and Toolkitsmentioning
confidence: 99%
“…Communities often had existing rules governing use of surface water sources, but had not developed effective rules to control groundwater use. When FES found that conventional "teaching" about groundwater management did not have a sufficient impact, they piloted games played by groups of farmers as experiential learning to help improve understanding and cooperation over groundwater (Ruth Meinzen-Dick et al 2016;Falk et al Forthcoming). In community debriefing after the games, participants discussed how the games related to their experiences with groundwater, and community resource persons presented information about water table trends.…”
Section: Tools and Toolkitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group dynamic games that simulate real-life resource use and multi-user interactions and connect social dilemmas to action situations have shown promise as an intervention tool for experiential learning about sustainable CPR management (Becu et al 2017, den Haan & van der Voort, 2018Ferrero et al, 2018). A growing body of literature explores the use of group games to facilitate engagement with communities to improve understanding of socioecological systems and stimulate discussions about the need and options to improve natural resource governance (Falk et al 2023). They are useful for identifying patterns in thinking and behavior, testing management options, as well as shaping "mental models" and understanding of relationships both among users and between users and the resource.…”
Section: Introductionmentioning
confidence: 99%
“…Participating communities were significantly more likely to adopt rules governing groundwater use, compared with control communities . While such games are not a silver bullet, they can complement other capacity support to shape mental models around groundwater resources and empower communities to strengthen local governance (Falk et al, 2023).…”
Section: Introductionmentioning
confidence: 99%